Pengaruh Pernikahan Dini Terhadap Kualitas Sumber Daya Manusia Pada Pembangunan Ekonomi Di Kabupaten Lombok Timur - Rina Sulistia Jamil; Subhan Purwadinata (CV. Ulil Albab Corp, 2024)
This research utilizes a descriptive research type with a quantitative approach using secondary time series data. The findings indicate that the poverty rate is one of the indicators for measuring the prosperity and quality of human resources in economic development, which significantly influences the occurrence of child marriage cases in East Lombok Regency. Additionally, several other factors that cannot be quantified are involved, such as internal factors originating from the child, cultural factors, social factors, environmental factors, and pregnancies outside of marriage.